FACTORS INFLUENCING CONSUMER REPURCHASE DECISION: A CASE STUDY OF SUKI TEE NOI - Satitpakeekul, Phatthira; Chothuang, Chomphunut; Koranee, Rattika; Chienwattanasook, Krisada (RMUTT GLOBAL BUSINESS ACCOUNTING AND FINANCE REVIEW, 2022)
The objectives of this research were to find how personal factors, brand equity, and service marketing mix factors influence consumer decision to repurchase Suki Tee Noi. The sample consisted of 400 consumers who experienced dining-in at Suki Tea Noi in Pathum Thani. Questionnaires were used to collect data. The obtained data were analyzed by using frequency, percentage, mean, and standard deviation. T-test, One-Way ANOVA, and multiple linear regression analysis (MRA) were used to test the hypotheses. The study shows that 1) personal factors: age, occupation, and average monthly income differently affected consumer decision to repurchase Suki Tee Noi products in Pathum Thani, 2) Brand equity factors: brand loyalty and brand awareness influenced consumers' decision to repurchase Suki Tee Noi in Pathum Thani, and 3) Service-marketing mix factors: service process, price, and marketing promotion influenced consumers' decision to repurchase Suki Tee Noi in Pathum Thani at a statistically significant level of .05. The brand equity and service-marketing mix factors together explained 65 percent of the variance in the repurchase decision.